(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Zooplankton is crucial dietary sources for omnivorous fishes and an essential component in freshwater food webs. A six-month investigation carried out from February to July 2023, encompassing three separate seasons, to examine the abundance and variety of zooplankton in connection to physico-chemical parameters in three different waterbodies: intensive, semi-intensive and extensive ponds at Chittagong University campus. Two ponds were chosen for each of the waterbodies that were classified. Monthly fluctuations of some physico-chemical parameters were noted. Most of the ponds were found to be alkaline and TDS, EC, and the variations of air and water temperature were also examined. Remarkable correlations observed between zooplankton and several physico-chemical parameters, either directly or indirectly. Zooplankton in Intensive ponds showed positive significant relationship with TDS (r=0.78, P< 0.1), EC (r=0.81, P< 0.05) and pH (r=0.34, P<0.1). Zooplankton demonstrated positive correlation with air temperature (r=0.61, P<0.1), TDS (r=0.38, P< 0.1) and EC (r=0.33, P<0.05) in semi-intensive ponds and all water parameters except TDS (r=-0.05, P<0.1) displayed strong significant link with extensive ponds. A total of 33 zooplankton species belonging to 19 genera with 3 classes were identified. Rotifers were the most prominent and abundant group of zooplankton, making up 76.75% to 86.49% of entire population and the most numerous genus was Brachionus. Copepods (5.88%-15.79%) and Cladocerans (2.35%-7.63%) were relatively abundant in three waterbodies. Semi-intensive and Extensive ponds showed maximum number of Rotifer abundance (35680u/l & 34980u/l) in summer season. Regarding copepod, maximum abundance were 1320u/l and 4560u/l in Intensive and Extensive ponds respectively during rainy season. Clodocera displayed sporadic abundance across several waterbodies and seasons, where’s Semi-intensive ponds showed maximum abundance in winter season (2680u/l). The current study revealed that extensive ponds had higher zooplankton production density than that of the Intensive and Semi-intensive ponds, with rotifers and copepods being most abundant in summer and rainy seasons, respectively. J Bangladesh Agril Univ 22(4): 517-529, 2024